A feasibility study of a psychoeducation intervention based on Human Caring Theory in nulliparous women with fear of childbirth. (2nd October 2021) - Boz, İlkay and Akgün, Mehtap and Duman, Ferdane
Abstract: Objective: To evaluate the effects of psychoeducation program based on the Human Caring Theory on the level of fear of childbirth (FOC) by comparing the antenatal education classes. Methods: This feasibility study was conducted in a single-blinded, randomized controlled trial on 24 nulliparous women with FOC between July and October 2018. The women received five sessions of psychoeducation and four sessions of antenatal education. The primary outcome was the level of FOC in prenatal period, and the secondary outcomes were the rate of preference for vaginal birth (VB) in prenatal period, the rate of VB, and the level of FOC in postnatal period. The level of the FOC was assessed using Wijma Delivery Expectancy/Experience Questionnaire A and B. Results: Although the levels of FOC of the women decreased in both groups for post-treatment, the decrease in the psychoeducation group was significantly higher compared to the antenatal education group ( p = 0.022). In the postnatal period, the level of FOC of psychoeducation group was statistically lower than that of the antenatal education group ( p = 0.000). Furthermore, all the women in the psychoeducation group and 58.33% of the women in the antenatal education group wanted to have a VB at the end of the program ( p = 0.012). However, there was statistically no difference between the groups in terms of the birth type ( p = 0.342). Conclusions: There seems to be an indication that the psychoeducation program based on Human Caring Theory might have a benefit to reduce the level of FOC of women compared to the antenatal education classes.